2005
DOI: 10.1111/j.1365-2834.2005.00553.x
|View full text |Cite
|
Sign up to set email alerts
|

Nursing agency and governance: registered nurses' perceptions

Abstract: Nurses' perceived lack of governance over their practice requires investigation and attention if occupational dissatisfaction, stress, turnover and low morale, which impact on quality care, are to be reduced. Dissatisfaction with nursing governance indicates a need to review nurses' professional involvement in clinical governance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
47
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(50 citation statements)
references
References 25 publications
(29 reference statements)
3
47
0
Order By: Relevance
“…McGillis Hall and Kiesners (2005) reported that regardless of how hard nurses worked, they were unable to handle their workloads. Staff frustration, unhappiness and low morale translate into lower care-standards (Attree, 2005;Begat et al, 2005). Overworked, stressed or burned-out healthcare professionals are more likely to deliver poor quality care.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…McGillis Hall and Kiesners (2005) reported that regardless of how hard nurses worked, they were unable to handle their workloads. Staff frustration, unhappiness and low morale translate into lower care-standards (Attree, 2005;Begat et al, 2005). Overworked, stressed or burned-out healthcare professionals are more likely to deliver poor quality care.…”
Section: Resultsmentioning
confidence: 99%
“…Throughout the review literature, overwhelming nursing workloads were detailed and their implications for quality outlined; with nurses attempting to maintain quality standards against the odds (Attree, 2005). McGillis Hall and Kiesners (2005) reported that regardless of how hard nurses worked, they were unable to handle their workloads.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This places governance on our professional agenda and emphasises the individual responsibility to engage in a culture of good governance. Attree (2005) agrees with this premise, concluding that health care professionals have a perceived lack of governance over their practice which requires investigation and attention if occupational dissatisfaction, stress, staff turnover and low morale, which impact on quality care, are to be reduced.…”
Section: Resultsmentioning
confidence: 77%